Pediatric bronchogenic cysts in the head and neck region: A study of 10 surgical cases and a review of the literature - Chen, Wei; Xu, MengRou; Wang, Qingyu; Xu, Hongming; Chen, Jiarui; Li, Xiaoyan (Frontiers in Pediatrics, 2022)
Objective: To investigate the clinical characteristics and surgical treatment outcomes of children with bronchogenic cysts (BCs) in the head and neck region. Methods: A retrospective study of 10 pediatric patients with BCs in the head and neck region treated in Shanghai Children’s Hospital during 2011 to 2022 was performed. Results: Ten patients with a final diagnosis of BCs in the head and neck region were identified based on their medical records. The most common location of the lesion was the neck (8 patients, 80%; 2 midline neck, 6 lateral neck), followed by the ventral tip of tongue (1 patient), and the posterior pharyngeal wall (1 patient). Misdiagnosed as lymphangioma in 5 cases, cyst in 3 cases, thyroglossal duct cyst in 2 cases and congenital pyriform sinus fistula in 1 case preoperative. The median follow-up period after surgery was 4.68 (range, 0.67～9.25) years. All ten of our patients underwent complete excision and did not experience recurrence or other complications. Conclusions: Although rare, BCs should be considered in the differential diagnosis of midline and lateral neck masses or intraoral cysts in children. Surgical excision of BCs is recommended and histopathology definitively confirms the diagnosis.